"A marketplace of schools": race, power, and education reform in the Detroit region. Issue 8 (14th September 2021) - Cohen, Dan
ABSTRACT: Over the past several decades market-based systems have increasingly been used to govern the delivery of urban services. Drawing on insights from the geography of markets, this paper investigates how market-based policies such as interdistrict choice and charter school programs have reshaped publicly funded schooling in the Detroit region. Through doing so it explores how market systems are made to align with the interests of actors who advance market structures that rework (rather than challenge) existing patterns of wealth and racial power. As described in this paper, such market systems must be understood as shaped by the economic, political, and social contexts they emerge from, with Detroit's regional context of segregation and anti-Black racism a key element guiding the creation of market institutions. Understanding markets in this manner allows insights into how the articulation of market logics with urban geographies shapes the lives of those who depend on urban services.